Switching lasers: learning curve of holmium laser enucleation of the prostate in surgeons experienced in thulium laser enucleation of the prostate - Wenk, Maren; Grüne, Britta; Hardenberg, Jost von; Hartung, Friedrich; Kowalewski, Karl-Friedrich; Rassweiler-Seyfried, Marie-Claire; Michel, Maurice Stephan; Herrmann, Jonas (Journal of endourology, 2022)
Objective: To evaluate perioperative parameters, clinical outcomes, and the learning curve of holmium laser enucleation of the prostate (HoLEP) in surgeons with experience in thulium laser enucleation of the prostate (ThuLEP). Materials and Methods: The learning curves for HoLEP of the first 50 consecutive patients of two surgeons experienced in ThuLEP were analyzed. In addition, demographic parameters, clinical outcomes, and adverse events (AEs) were evaluated. Results: Mean operation time was 70.9 ± 29.7 minutes (standard deviation) (Surgeon 1) and 74.4 ± 35.4 minutes (Surgeon 2), the mean enucleation efficiency was 1.5 ± 0.6 g/min (Surgeon 1) and 1.5 ± 0.7 g/min (Surgeon 2). The hemoglobin loss was 0.9 ± 0.8 and 0.8 ± 0.8 g/dL. For both surgeons, there was a significant learning curve in enucleation efficiency within the first 50 cases (Surgeon 1: p = 0.034, Surgeon 2: p = 0.006, both: p = 0.0003, Spearman's ρ = 0.351). Both surgeons started with an enucleation efficiency of around 1 g/min in their first 10 cases. No significant correlation between hemoglobin loss and experience could be found (p = 0.823, ρ = 0.025). While there was no significant learning curve for morcellation efficiency (p = 0.785, ρ = 0.028), a significant progress was found for one of the two surgeons regarding laser energy efficiency (p = 0.014). The overall incidence of all grade treatment-related AEs was low at 10.0%, and extremely low for significant complications with Clavien-Dindo Grade >II at 1%. Conclusions: In our analysis, switching to HoLEP is uncomplicated and safe for experienced ThuLEP surgeons. The enucleation efficiency was high from the beginning, but a learning curve was present for both surgeons. No learning curve was noticeable in hemoglobin loss and the incidence of complications, both of which were low throughout the study.
Gesehen am 17.07.2023